Butterfly Therapy in Improving Self-Acceptance Among Female Students at State High School 1ngaglik - Alifian Nur Hidayat; Ridha Wahyuni (Eduvest - Journal of Universal Studies, 2024)
Adolescence is often characterized by complex emotional dynamics and identity formation, including issues of self-image and self-acceptance. When the discrepancy between an ideal self-image and self-reality is not managed well, various negative psychological symptoms can emerge. Self-acceptance becomes a crucial aspect in building stable mental health in adolescents. Butter fly Therapy is a simple yet effective approach aimed at increasing emotional calmness and self-awareness. This research seeks to examine the influence of Butter fly therapy on the improvement of self-acceptance among high school female students. A quantitative approach with a quasi-experimental design was used, involving two groups (experimental and control) with a total of 34 participants. The instrument used was Berger's Self-Acceptance scale. The analysis results show that the t-test results can be interpreted as follows:  The t-test results for Butterfly Hug Therapy show that the t-value of 11.043 is greater than the table t-value of 1.739 (8,002 > 1.739) and the significance value of 0.000 is greater than the significance level of 0.05. This indicates that Butterfly Hug Therapy has an effect on increasing self-acceptance among female students at Ngaglik 1 State High School.